A m6Avalue predictive of prostate cancer stemness, tumor immune landscape and immunotherapy response. Issue 1 (25th March 2022) - Zou, Cheng; He, Qinju; Feng, Yuqing; Chen, Mengjie; Zhang, Dingxiao
Abstract: The molecular mechanisms underpinning prostate cancer (PCa) progression are incompletely understood, and precise stratification of aggressive primary PCa (pri-PCa) from indolent ones poses a major clinical challenge. Here, we comprehensively dissect, genomically and transcriptomically, the m 6 A ( N 6 -methyladenosine) pathway as a whole in PCa. Expression, but not the genomic alteration, repertoire of the full set of 24 m 6 A regulators at the population level successfully stratifies pri-PCa into three m 6 A clusters with distinct molecular and clinical features. These three m 6 A modification patterns closely correlate with androgen receptor signaling, stemness, proliferation and tumor immunogenicity of cancer cells, and stroma activity and immune landscape of tumor microenvironment (TME). We observe a discrepancy between a potentially higher neoantigen production and a deficiency in antigen presentation processes in aggressive PCa, offering insights into the failure of immunotherapy. Identification of PCa-specific m 6 A phenotype-associated genes provides a basis for construction of m 6 Avalue to measure m 6 A methylation patterns in individual patients. Tumors with lower m 6 Avalue are relatively indolent with abundant immune cell infiltration and stroma activity. Interestingly, m 6 Avalue separates PCa TME into fibrotic and nonfibrotic phenotypes (instead of previously reported immune-proficient or -desert phenotypes in other cancer types). Significantly, m 6 Avalue can be used to predict drug response and clinical immunotherapy efficacy in both castration-resistant PCa and other cancer types. Therefore, our study establishes m 6 A methylation modification pattern as a determinant in PCa progression via impacting cancer cell aggressiveness and TME remodeling. Graphical Abstract: